Forged in hell : the gripping true story of the special forces heroes who broke the Nazi stranglehold - Lewis, Damien (Citadel Press, Kensington Publishing Corp., 2024)
In the summer of 1943, the largest invasion fleet ever assembled sailed for fortress Europe, aiming to bulldoze its way onto Nazi shores. At its vanguard went a few hundred elite forces soldiers, the Royal Navy warship carrying them bearing the iconic winged dagger emblem on its prow, plus the motto 'Who Dares Wins'. Led by the legendary SAS commander Blair 'Paddy' Mayne, these war-bitten, piratical raiders were tasked to do the impossible - to bludgeon their way through the most heavily defended enemy shoreline, so enabling the ensuing forces to follow on. If they succeeded, it would mark the turning point in the war. If they failed, the consequences were unthinkable. Against all odds, outnumbered some fifty-to-one, and facing a ferocious series of cliffside defences, they would have to dare all as never before. So begins the incredible true story of the SAS's mission to liberate Europe. Replete with surprise, shock, action, heroic endeavour and glory, not to mention subterfuge, treachery and dismay, this is a classic combination of combat writing and breath-taking narrative non-fiction.